Advances in food science, sustainable agriculture, and agroindustrial engineering - Universitas Brawijaya. Fakultas Teknologi Pertanian (Faculty of Agricultural Technology, Universitas Brawijaya, 2018)
Aimed to diseminate the results and the progress in research, science and technology relevant to the area of food sciences, agricultural engineering and agroindustrial engineering.
Keywords: Agricultural engineering : Periodicals; Agricultural engineering : Indonesia : Periodicals; Food industry and trade : Periodicals; Food industry and trade : Indonesia : Periodicals; Food industry and trade; Agricultural engineering; Indonesia